(untitled) (European Journal of Health Research, 2020)
The body is a social construction subject to multiple representations. These representations give sense and significance to its morphology and change in line with historical, social and cultural contexts. The bodies of women with breast cancer undergo important changes in the course of their treatment. These changes have not only physical consequences but also psychological and social ones. Study objectives: (1) to understand the process of the body’s configuration and reconfiguration in the period of illness in women with breast cancer; (2) to analyse these women’s experiences of the changes in their bodies during their treatment for breast cancer. Methodology adopted: qualitative, based on semi-structured interviews with women with breast cancer. Findings: the women’s accounts reveal psychological and social consequences stemming from the changes brought about in their bodies by their treatment. Conclusion: the study evidences the compelling need for the team of health professionals to address the body in the caring process of breast cancer treatment.